Study of risk factors associated with development of severe respiratory distress in the new born - Patil, Sandeep; Halkude, Varsha; Tondare, Mahesh; Mudaglimath, Anand (International Journal of Contemporary Pediatrics, 2018)
Background: As Transient tachypnea of newborn is the most common cause of Respiratory distress and significant number of newborns with respiratory distress develops severe respiratory insufficiency requiring intensive monitoring. With these points, we undertake to identify risk factors associated with development of severe respiratory distress in the new born. Methods: Hundred newborns that were having respiratory distress within 72 hours of birth admitted to NICU were included in the present study. The severity of respiratory distress was noted according to risk factors and clinical assessment. The details were noted in all the newborns- General information, history, risk factors and clinical examination findings of mother and newborn were documented. Results: In the present study, 62.5% of the newborns born to Primigravida mothers developed severe respiratory distress. In the present study it was seen that 83.6% of newborns with SGA developed severe respiratory distress compared to 60% and 33.3% newborns with LGA and AGA respectively. It was seen that the risk of neonatal respiratory distress markedly increased with decreasing birth weight (p<0.001). Conclusions: Immediate clinical outcome of newborn respiratory distress in term of mortality rate is variable and depends on the cause of newborn distress.